Investigating the link between APCI1307K mutation and breast cancer in a Jordanian Arab population - Sharaf, Baha; Bani Hani, Hira; Zayed, Anas; Barbar, Maha; Khater, Suhaib; Hushki, Ahmad; Abdel-Razeq, Rashid; Titi, Mohammad; Al-Halalsheh, Reem; Mahafdah, Suleiman; Ashour, Lin; Abdel-Razeq, Hikmat (Frontiers in Oncology, 2025)
IntroductionAPCI1307K missense mutation, welldescribed in Ashkenazi Jewish, is commonly encountered among Jordanian patients with solid tumors. In this study, we investigated the potential association between the APC gene (I1307K variant) and the risk of breast cancer among Jordanian Arab patients.MethodsAll newly diagnosed patients with solid tumors were offered participation in a universal germline genetic screening study utilizing an investigational 84-gene panel. Patients were categorized based on whether they met or did not meet the criteria outlined in the National Comprehensive Cancer Network (NCCN) for genetic testing.ResultsAmong the screened cancer patients (n = 3,319), 136 (4.1%) had APCI1307K. Breast cancer was the most common primary tumor (n = 56, 41.2%). Among them, 41 (73.2%) had a screening colonoscopy, and 12 (29.3%) were found to have colorectal polyps, while 41.7% (5/12) had low-grade dysplasia. Of the 34 (25.0%) patients diagnosed with colorectal cancer, 23 (67.6%) exhibited tumors presenting as polyps, had concomitant polyps, or displayed background abnormalities with a polypoid nature.DiscussionThese findings suggest that Arab individuals with the APCI1307K missense mutation are at higher risk of breast and familial colorectal cancers. The APCI1307K missense variant holds promise in informing screening and cancer prevention strategies. However, additional confirmation by larger studies is needed.